Effectiveness of promotion strategies used by Pusat Zakat Negeri Sembilan in creating an awareness Muslims to pay zakat / Noorbaizura Mohd Saaid @ Lajis - Mohd Saaid @ Lajis, Noorbaizura (Faculty of Business and Management, 2009)
This study examined the effectiveness of the of the Promotion Strategy Tools (PST) as predictor factors in creating the awareness among Muslim to pay zakat. PST consist of four variables included Advertising (ADV), public relation (PR), personal selling (PS) and sale promotion (SP). Dependent variable in this study was Awareness among Muslim to pay zakat (AMZ). This study used correlation research design. Simple random sampling was used to get sample from this study. Data were obtained from 40 working Muslim out of 50 respondents from government and private sector in Seremban Town. The analysis used was central tendency statistics, correlation and regression analysis. Analysis showed that 95% respondents pay zakat and most of them are female. Majority of the zakat payer was government officer. Finding of this study indicated that all the independent variables including Advertising (ADV), public relation (PR), personal selling (PS) and sale promotion (SP) were significantly positive relationships with Awareness among Muslim to pay zakat (AMZ). This study also found that Advertising (ADV) and Sales Promotion (SP) were the significantly good predictor factors in creating the Awareness among Muslim to pay zakat (AMZ). Study concludes that regression model developed from this study shows that 93% variation of the dependent variables explained by independent variables. The Study suggested that advertising activities should be more emphasized in order to realize people the importance of zakat and the sale person in the organization PZNS should be train and retrained to be more competitiveness. It also suggested that sales people should be explored internally and externally to gain valuable experience especially in marketing. The study suggests that future research should be conducted by using more independent variables to look the effectiveness towards sales or zakat.